Students’ and Lecturers’ Perceptions of Neuro-Linguistic Programming-Integrated Masked Language Model Twenty-Four Implementation in Test of English as a Foreign Language Learning - Lollo Rosa Lubis; Jubaida Ritonga; Idris Saputra; Maldini Alfarizi; Friska Dani (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines students’ and lecturers’ perceptions of the implementation of the Natural Language Processing (NLP)-integrated Marsiadapari Learning Model (MLM-24) in TOEFL learning at Institut Pendidikan Tapanuli Selatan. MLM-24 is a collaborative learning model rooted in the Batak Toba tradition of mutual cooperation. This study employed a mixed-method approach using questionnaires and semi-structured interviews. The findings indicate that the model improves students’ understanding of TOEFL materials, motivation, confidence, and collaborative engagement. NLP integration supports grammar analysis, syntactic understanding, and automated feedback, enabling students to better comprehend complex linguistic structures. However, challenges such as time management and unequal participation were identified. Overall, the NLP-integrated MLM-24 provides a balanced approach by combining cultural values, collaborative learning, and technology to enhance TOEFL learning outcomes.